Procedure Determination and Symbolic Equation Analysis as Predictors of Higher Order Thinking Skills in Physics Problem Solving - Rabiudin Rabiudin (SEARCH: Science Education Research Journal, 2025)
Higher-order thinking skills (HOTS) constitute essential competencies in 21st-century physics education, particularly in problem-solving contexts that require analytical, evaluative, and reflective reasoning. This study investigates the extent to which procedure determination skills and symbolic equation analysis jointly predict students’ HOTS in physics problem solving. A quantitative correlational design was employed, involving 50 undergraduate students enrolled in a Science education program. Data were collected using Likert-scale instruments designed to measure procedural determination skills, symbolic equation analysis, and HOTS in physics problem solving. The data were analyzed through descriptive statistics, measurement model evaluation (including validity and reliability testing), and multiple linear regression to examine the simultaneous predictive effects of the two independent variables on HOTS. The findings indicate that both procedure determination skills and symbolic equation analysis are positively associated with students’ HOTS, with symbolic equation analysis demonstrating a relatively stronger contribution. However, when considered simultaneously, the two predictors explain only a limited proportion of variance in HOTS and do not yield a statistically significant joint effect. These results suggest that higher-order thinking in physics problem solving represents a multidimensional construct that cannot be sufficiently explained by procedural and symbolic competencies alone. This study highlights the necessity of instructional approaches and future research that integrate conceptual understanding, metacognitive regulation, and contextual reasoning to more effectively foster HOTS in physics education.